(untitled) (UCC Student Medical Journal, 2024)
Introduction This case report examines a 6-year-old male patient, NN, with a complex presentation of impetiginized atopic dermatitis. The report adopts a biopsychosocial approach, considering the interplay of biological, psychological, and social factors influencing the patient’s condition and management. Methods The case study methodology involved a comprehensive review of NN’s medical history, family background, and current clinical presentation. A multidisciplinary approach was employed, integrating insights from dermatology, pediatrics, psychology, and social work to holistically address the patient’s needs. Results Biologically, NN’s condition was characterized by severe exacerbation of atopic dermatitis, likely triggered by environmental pathogens and compounded by iron-deficiency anemia. Psychologically, the severity of his skin condition led to increased irritability and social withdrawal, a notable deviation from his previously cheerful temperament. Social considerations highlighted the supportive family environment and the challenges posed by the visible nature of his skin lesions, affecting his school attendance and potential social stigma. Discussion The case underscores the intricate relationship between biological predispositions, psychological resilience, and social environmental factors in managing pediatric atopic dermatitis. It highlights the importance of a multidisciplinary approach in treating such complex cases, considering not only the physical but also the emotional and social wellbeing of the patient. Conclusion NN’s case demonstrates the critical need for an integrated biopsychosocial approach in pediatric dermatology, particularly in complex cases like impetiginized atopic dermatitis. Tailoring treatment to address the multifaceted aspects of the patient’s condition can lead to more effective management and improved quality of life for both the patient and their family.